1999
DOI: 10.1007/s001130050402
|View full text |Cite
|
Sign up to set email alerts
|

The significance of intracompartmental pressures in diagnosing chronic exertional compartment syndrome - A metaanalysis of studies monitoring dynamic anterior compartment pressures during exercise

Abstract: From all studies no uniform recommendation for parameters of diagnostic relevance can be derived. On this background it should be demanded that future research is conducted by a uniform regimen for examination and modern technique of measuring with a high temporal resolution. Under these standardised conditions the investigated parameters of the intracompartmental pressure curve should be reconsidered once more regarding diagnostic predictability by calculations of specifity and sensitivity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 0 publications
0
4
0
1
Order By: Relevance
“…55 Pressure measurements vary in some cases up to 500% potentially because of operator experience, catheter type, volume of instilled fluid, and the depth of catheter placement. 5,33,59 Obviously, measurement reliability is enhanced by using a single experienced tester and following standardized procedures as employed in this study (intraclass correlation coefficient, .86). Regardless of whether a clinician uses pressure measurements, a positive pressure test result alone is not sufficient to make a diagnosis of CECS and should never replace a meticulous history and comprehensive physical examination.…”
Section: Discussionmentioning
confidence: 99%
“…55 Pressure measurements vary in some cases up to 500% potentially because of operator experience, catheter type, volume of instilled fluid, and the depth of catheter placement. 5,33,59 Obviously, measurement reliability is enhanced by using a single experienced tester and following standardized procedures as employed in this study (intraclass correlation coefficient, .86). Regardless of whether a clinician uses pressure measurements, a positive pressure test result alone is not sufficient to make a diagnosis of CECS and should never replace a meticulous history and comprehensive physical examination.…”
Section: Discussionmentioning
confidence: 99%
“…Two extensive review articles4 29 discuss 16 and 21 studies respectively and provide excellent summaries of the literature and both essentially conclude that there is no consensus for diagnostic pressure or exercise regimes used. The 2006 survey by Tzortziou et al 30 of UK orthopaedic surgeons reported that 42% used a dynamic compartment pressure (ie, during exercise) >35 mm Hg as the criterion for anterior CECS diagnosis and 35% used Pedowitz's modified criteria.…”
Section: Introductionmentioning
confidence: 99%
“…2,10,15,16 Although history and physical examination may raise the suspicion of CECS, it is generally very difficult to exclude other causes of lower leg pain during exercise, even for those who are highly experienced in this field. 6,13,23 Therefore, the diagnosis is usually confirmed by intramuscular pressure measurement, preferably after exercise. 14,17,18 To obtain this pressure measurement, a needle or catheter is introduced through the skin and fascia into the muscular compartment.…”
mentioning
confidence: 99%